Individual and socio-cultural factors influencing male involvement in family planning decision-making among men attending Ndejje Health Center IV, Wakiso District. A cross-sectional study. - Nakimuli , Joselyne; Mayanja, Edrine; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Ssemuwemba, Francisco; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background: The study aimed to determine the individual and socio-cultural factors influencing male involvement in family planning decision-making among men attending Ndejje Health Center IV, Wakiso District. Methodology: This descriptive cross-sectional quantitative study was conducted at Ndejje Health Centre IV, Wakiso District, to assess male involvement in family planning decision-making. A sample of 50 men was calculated using the Kish and Leslie (1965) formula at a 95% confidence level with a 10% non-response rate. Participants were conveniently selected. Data were collected over five days using structured researcher-administered questionnaires covering demographic, individual, and sociocultural factors. Data were analyzed with Microsoft Excel and presented as frequencies and charts. Validity, reliability, ethical approval, informed consent, confidentiality, and voluntary participation were ensured. Results: The study included 50 men attending Ndejje Health Centre IV. Most respondents were aged 39-58 years (58%), while 16% were aged 59 years and above. A large proportion were cohabiting (40%), followed by singles (32%) and married men (16%). Nearly half were businessmen (46%), and 38% had attained secondary education, while 14% had no formal education. All respondents (100%) were aware of family planning methods. However, 78% reported unstable income, and 4% had no income. Although 82% personally supported family planning, 70% believed women are mainly responsible for FP decisions. More than half (54%) felt men have no role in FP, 76% sometimes avoided FP discussions due to stigma, 94% lacked social support, and 76% reported no religious encouragement for male involvement. Conclusion: Men's involvement in decision-making remained low due to unstable income and persistent socio-cultural barriers such as stigma, lack of social and religious support, and the belief that family planning is primarily a woman’s responsibility. Recommendation: The Ministry of Health should prioritize the integration of male-focused reproductive health programs.